Analisis Pengaruh Cash Turnover, Receivable Turnover, Inventory Turnover terhadap Profitability: Studi Kasus pada Perusahaan Sub Sektor Konstruksi Bangunan yang terdaftar di Bursa Efek Indonesia Periode 2018-2022 - Afrianita Ashri; Fathihani (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2023)
The purpose of this study was to determine the effect of Cash Turnover, Receivable Turnover, and Inventory Turnover on Profitability in Building Construction Sub Sector Companies in Indonesia. The variable used is Return on Assets as the dependent variable and the independent variable is Cash Turnover, Receivable Turnover, and Inventory Turnover. The sample used in this study is a company listed in the building construction sub-sector on the Indonesia Stock Exchange. Samples were selected using purposive sampling. From a population of 50 companies listed in the building construction sector on the IDX. There were 38 companies that did not pass the purposive sampling selection so the sample used in this study was 12 companies.